Shi jie xi huan zhe yang de ni = The world needs who you were made to be - Gaines, Joanna 1978- (Yuan liu chu ban shi ye gu fen you xian gong si, 2021)
In the #1 New York Times bestseller, 'The world needs who you were made to be', Joanna Gaines celebrates how creativity and acceptance can come together to make for a bright and beautiful adventure. The book, illustrated by Julianna Swaney, follows a group of children as they each build their very own hot-air balloons. As the kids work together, leaning into their own skills and processes, we discover that the same is true for life—it's more beautiful and vibrant when our differences are celebrated.
In chinesischer Schrift mit Umschrift in Fu yin zhu hao/ Guo yu zhu yin
Keywords: Self-acceptance / Juvenile literature; Individual differences / Juvenile literature; Sociology / Juvenile literature; Acceptation de soi / Ouvrages pour la jeunesse; Caractéristiques individuelles / Ouvrages pour la jeunesse; Sociologie / Ouvrages pour la jeunesse; Bilderbuch